Drug Addiction and the Most Important Diseases that affect Human Mental, Mental and Physical Health in Iraqi Society (Indian Journal of Forensic Medicine & Toxicology, 2020)
First: Problem and Importance of search The effects of psychological, health, mental and physical are serious diseases that affect the individual drug user was not the drug of this age has been known by man since ancient times and fought ancient societies medically, culturally, socially and religiously Human life from the deterioration of his health and his illnesses complex mental health, mental and physical Second: Goals of search Drug addiction and the most important diseases that affect human mental, mental and physical health in Iraqi society. Third: Society and sample of search The study sample was selected on two middle schools in Al-Hilla city (Imam Ali School for Boys and Bint Al-Huda School for Girls). 100) Researched and used the method of social survey method intentional sample and questionnaire, interview, observation, participation and statistical methods and hypotheses and the most important treatments for addicts are psychological, health, mental, physical and social treatment.